UV degradation characteristics of GPI standard pipes: Regarding external UV deterioration of GPI standard lamination of centrifugal molded tube (J) (GPI Journal, 2023)
The outer surface of the GPI standard laminated product of centrifugally formed pipes used for oil-based pipes, etc. can withstand deterioration due to ultraviolet rays and contact wear for more than 40 years. The applicable resin consists of an exterior laminated structure consisting of urethane-modified epoxy resin (vinyl ester), inorganic pigments (titanium oxide, etc.), and glass fiber mat (200#CSM), and the centrifugal force of centrifugal molding is 40G or more and it is in a centrifugal state. Since the outer surface of the cured product is formed by centrifugation of the ultraviolet absorber, it has been found that there is very little UV deterioration of the outer surface of the tube.